Portraits : the Hasidic legacy of Elie Wiesel - Patterson, David, 1948- (SUNY series in contemporary Jewish thought., 2021)
"Explores Elie Wiesel's portraits of the sages of Judaism and elaborates on the Hasidic legacy from his life and his teaching"--